PENGARUH PERENCANAAN PAJAK, LEVERAGE, PROFITABILITAS DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (Studi Perusahaan Manufaktur Yang Terdaftar Di BEI Pada Tahun 2012-2014) - Eko Satriyo, 12.05.52.0217; Setyowati, Widhy (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to analyze the effect of tax planning leverage profitability and deferred tax expense. Identification of the companies that perform earnings management practices carried out by applying the profit distribution approach. Income distribution approach identifies earnings reporting limits and find companies that are below the limits earnings reporting will try to pass these limits by earning management The population in this study are all companies listed in Indonesia Stock Exchange in the year 2012 to 2014. The sample used in this study are all manufacturing companies. The total sample for the three years of observation is 96 samples. Sampling in this research is done by using purposive sampling technique. Purposive sampling is a sampling of the population deliberately based criteria. The results showed that tax planning, leverage, and the deferred tax expense significant negative effect on earnings management and based on the result showed that the profitability of significant positive effect on earnings management. Â Keywords: Earnings Management, Tax Planning, Leverage, Profitability, Deferred Tax Expense